Jane Jacobs' 'Cities First' Model and Archaeological Reality. (17th April 2014) - Smith, Michael E.; Ur, Jason; Feinman, Gary M.
Abstract In The Economy of Cities, Jane Jacobs conjectured that the world's first cities preceded the origins of agriculture, a proposition that was most recently revived by Peter Taylor in the pages of this journal. Jacobs' idea was out of line with extant archaeological findings when first advanced decades ago, and it remains firmly contradicted by a much fuller corpus of data today. After a review of how and why Jacobs formulated her 'cities first' model, we review current archaeological knowledge from the Near East, China and Mesoamerica to document the temporal precedence of agriculture before urbanism in each of these regions. Contrary to the opinions of Jacobs and Taylor, archaeological data are in fact sufficiently robust to reconstruct patterns of diet, settlement and social organization in the past, and to assign dates to the relevant sites. Our response illustrates how generations of archaeological discoveries have yielded solid empirical foundations for the evaluation of wider social scientific debates.